Single Nucleotide Polymorphisms of Porcine lncMGPF Regulate Meat Production Traits by Affecting RNA Stability - Lv, Wei; Zhao, Shiyu; Hou, Yunqing; Tong, Qian; Peng, Yaxin; Li, Jianan; Xu, Zaiyan; Zuo, Bo (Frontiers in Cell and Developmental Biology, 2021)
lncMGPF is a novel positive regulator of myogenic differentiation, muscle growth and regeneration in mice, pigs and humans. But whether natural mutations within lncMGPF gene regulate animal meat production traits is unclear. In this study, 10 single nucleotide polymorphisms (SNPs) of pig lncMGPF gene were identified among 10 pig populations including commercial pig breeds and Chinese local pig breeds. These SNPs are highly linked and constructed into multiple haplotypes, and haplotype ATTCATGTTC (H1) mainly exists in commercial pig breeds while haplotype GCCTGCACCT (H3) is more frequent in Chinese local breeds. Association analysis indicated that these 10 SNPs are significantly associated with the backfat thickness and loin muscle area (P<0.05) respectively, and homologous H1 individuals have higher loin muscle area and lower backfat thickness than homologous H3 pigs. Bioinformatics and functional analysis showed that H1 has a longer half-life and more stable RNA secondary structure than H3. And plncMGPF haplotype H1 has stronger effects on pig primary myogenic progenitor cells differentiation and muscle growth compared with plncMGPF haplotype H3. Our observation suggested that the SNPs in lncMGPF can change the RNA stabilities and lncMGPF function, thereby affecting the meat production traits of pigs.